The conductors - Glover, Nicole (Murder & magic ;, 2021)
Hetty Rhodes and her husband, Benjy, were Conductors on the Underground Railroad, ferrying dozens of slaves to freedom with daring, cunning, and magic that draws its power from the constellations. With the war over, those skills find new purpose as they solve mysteries and murders that white authorities would otherwise ignore. In the heart of Philadelphia's Seventh Ward, everyone knows that when there's a strange death or magical curses causing trouble, Hetty and Benjy are the only ones that can solve the case. But when an old friend is murdered, their investigation stirs up a wasp nest of intrigue, lies, and long-buried secrets- and a mystery unlike anything they handled before. With a clever, cold-blooded killer on the prowl testing their magic and placing their lives at risk, Hetty and Benjy will discover how little they really know about their neighbors...and themselves.